Work advisability evaluation of transport and logistic centerin the transport service market - Павленко, Олексій Вікторович; Потаман, Наталія Володимирівна; Калініченко, Олександр Петрович; Гонтаренко, Юлія Олександрівна (Technology audit and production reserves, 2014)
The technique of work feasibility evaluation of the transport and logistic center in the transport service market, allowing to select the best package for maximum profit is developed. The presented object of study allowed to determine its structure, internal communication between the system elements, as well as input parameters: the number of services provided by the transport and logistics center, consignment volume, transport distance, ordering interval and output parameters of the system - the maximum profit. Based on the analysis of the ordering flow in the "IRBIS-AUTO" LTD it is determined, that the consignment volume is distributed by normal distribution low of random variables, and the ordering interval and the transport distance - according to an exponential distribution law. The received regression models and profit calculations for each package of services for different values of the expectation allow to select the optimum service package.